2020
DOI: 10.3390/s20164575
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis on Machine Learning and Deep Learning to Predict Post-Induction Hypotension

Abstract: Hypotensive events in the initial stage of anesthesia can cause serious complications in the patients after surgery, which could be fatal. In this study, we intended to predict hypotension after tracheal intubation using machine learning and deep learning techniques after intubation one minute in advance. Meta learning models, such as random forest, extreme gradient boosting (Xgboost), and deep learning models, especially the convolutional neural network (CNN) model and the deep neural network (DNN), were trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 34 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…Regarding the training data time length, Lee et al ( 20 ) studied the intra-operative AHE scenario and found 3 min of data performed better than 2 and 1 min. It is not difficult to imagine that a shorter prediction window and a longer training data time would provide better prediction accuracy, but a prediction window that is too short would be clinically less valuable to healthcare providers in terms of providing them with sufficient time to check the patient's situation and decide if an intervention is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the training data time length, Lee et al ( 20 ) studied the intra-operative AHE scenario and found 3 min of data performed better than 2 and 1 min. It is not difficult to imagine that a shorter prediction window and a longer training data time would provide better prediction accuracy, but a prediction window that is too short would be clinically less valuable to healthcare providers in terms of providing them with sufficient time to check the patient's situation and decide if an intervention is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the most used number of features is between 2 and 9, as shown in Figure 4 (right panel). Lee et al ( 20 ) compared the use of vital records with the use of vital records plus electronic health records (EHR), and found that for the convolutional neural network model, EHR improves the accuracy by 0.39%; however, for other algorithms, such as RF, Xgboost, and deep neural network, the differences were negligible. Therefore, with these completely different findings, it is difficult to conclude which methodology is the best for extracting the features, what features are universally effective no matter what algorithms are applied, or how feature reduction impacts prediction performance.…”
Section: Discussionmentioning
confidence: 99%
“…It is based on a logistic regression and uses engineered features derived from the 20-second arterial waveform as input [ 4 ]. Other researchers have attempted to predict postinduction hypotension using either machine- or deep-learning technologies [ 5 , 25 ]. However, conventional machine-learning technologies require manually engineered features extracted from raw data because they lack the ability to process raw data [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…After a comprehensive review of different ML prediction algorithms reported in the literature, compared the scalable, flexible, accurate, and relatively fast, five types of supervised ML classifiers were selected to provide for the establishment the prediction model in EGC (33)(34)(35)(36)(37). These models were the logistic regression classifier (LRC), linear support vector classifier (Linear SVC), Gaussian process classification (GPC), and two gradient boosting methods extreme gradient boosting (XGBoost) and light gradient boosting machine (LightGBM).…”
Section: Modelsmentioning
confidence: 99%